1990
DOI: 10.1038/hdy.1990.87
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in allele frequencies in the pollen pool of Eucalyptus rhodantha

Abstract: 6065.Investigation of the mallee Eucalyptus rhodantha which has an irregular, protracted flowering period demonstrated that individual plants differ in fecundity and phenology and that allele frequencies in the pollen pool change during the flowering season. Allele frequencies of the pollen pool were estimated by several methods which either assumed temporal homogeneit1 or took flowering phenology into account. These allele frequencies were compared for their abilities to estimate r. The estimates of t based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A number of studies have, however, documented temporal shifts in allele frequencies in the pollen pool (e.g. Fripp et al 1987;Sampson et al 1990). These shifts imply genetic differences among plants flowering at different times, but they do not confirm IBT because individual plants can contribute disproportionately to the pollen pool.…”
Section: Empirical Evidencementioning
confidence: 99%
“…A number of studies have, however, documented temporal shifts in allele frequencies in the pollen pool (e.g. Fripp et al 1987;Sampson et al 1990). These shifts imply genetic differences among plants flowering at different times, but they do not confirm IBT because individual plants can contribute disproportionately to the pollen pool.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Eighty-three plants (41.4%) are estimated to have been capable of flowering in the entire population during the 1992 flowering season, but the number releasing pollen at any one time would be considerably less, because large-flowered eucalypts have staggered flowering over long seasons. In E. rhodantha for example, although most plants had buds, no more than 50% of plants were flowering at the peak of the season (Sampson et al, 1990). Indeed, some plants may finish flowering before others begin.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the StAMOVA is a general linear model, any number of additional external factors and interactions among external factors can be easily added to the model just as in a multiple regression analysis. For example, in addition to the density of local pollen donors, the degree of phenological overlap has also been shown to influence pollen pool composition significantly (eg, Sampson et al, 1990;Adams and Birkes, 1991). By sampling across a range of densities in the degrees of phenological overlap, one could isolate the importance of each of these factors as well as their interaction in shaping the distribution of genetic structure within spatially separated pollen pools.…”
Section: Discussionmentioning
confidence: 99%
“…Further, several studies of forest tree mating systems have reported the effects of local pollen donor density on pollen pool composition (eg, Farris and Mitton, 1984;Knowles et al, 1987;Shea, 1987;Murawski and Hamrick, 1991). Additional factors such as flowering phenology (Sampson et al, 1990), adult allele frequency gradients (Dyer and Sork, 2002), elevation gradients (Loechelt and Franke, 1996), and inbreeding and spatial autocorrelation among adult individuals (Austerlitz and Smouse, 2001b) also act to increase the genetic divergence among sampled pollen pools. If any of these factors have a significant influence on pollen pool composition, then estimates of pollen dispersal distance will be biased downward.…”
Section: Introductionmentioning
confidence: 99%